Message from the President of the United States [electronic resource] : transmitting a letter from the Secretary of State, with accompanying papers, touching the subjects in dispute between the government of the United States and the government of Great Britain in the Behring Sea, including all communications since March 4, 1889. - United States. Dept. of State.; United States. President (1889-1893 : Harrison). (Washington : G.P.O., 1890)
At head of title : Seal fisheries of Behring Sea. "51st Congress, 1st session. House of Representatives. Ex. Doc. no. 450"-p. [1]. Electronic reproduction. Mode of access: Internet. 44